2000
DOI: 10.1128/aac.44.5.1140-1145.2000
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Trends in Enteropathogenic Bacteria Isolated in 1985–1987 and 1995–1998 in Barcelona

Abstract: Trends in resistance to antimicrobial agents used for therapy have been evaluated with 3,797 enteropathogenic bacteria, Campylobacter, Salmonella, Shigella, and Yersinia, between 1985-1987 and 1995-1998. The greater increase in the rate of resistance was observed in Campylobacter jejuni for quinolones (from 1 to 82%) and tetracycline (from 23 to 72%) and in gastroenteric salmonellae for ampicillin (from 8 to 44%), chloramphenicol (from 1.7 to 26%), and trimethoprim-sulfamethoxazole and nalidixic acid (from les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
7
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 32 publications
10
67
7
1
Order By: Relevance
“…The data reported here demonstrate a high level of drug resistance (98.5% [66 of 67 strains]) associated with S. enterica serotype Typhimurium, a result which correlates with those of studies performed in the European Union (6,14,30,22). Multidrug resistance was observed in 88% (59 of 67) of S. enterica serotype Typhimurium strains, and the resistance profile for 77.6% (52 of 67) of these strains was ACSSuT.…”
supporting
confidence: 74%
“…The data reported here demonstrate a high level of drug resistance (98.5% [66 of 67 strains]) associated with S. enterica serotype Typhimurium, a result which correlates with those of studies performed in the European Union (6,14,30,22). Multidrug resistance was observed in 88% (59 of 67) of S. enterica serotype Typhimurium strains, and the resistance profile for 77.6% (52 of 67) of these strains was ACSSuT.…”
supporting
confidence: 74%
“…A contributing factor for resistance dissemination observed in certain Salmonella serotypes has been the unnecessary use of antimicrobials for self limited gastroenteritis treatment. It has been suggested that these treatments be reserved only for extraintestinal salmonellosis and in cases of child gastroenteritis or elderly and immune suppressed patients where antibioticotherapy is fundamental to control these diseases (Winokur et al, 2000;Prats et al, 2000). Regarding antimicrobials resistance of enteric pathogens, the most worrying factor has been the increase of multiresistance dissemination of S. typhimurium and also, on a smaller scale, by other serotypes due to the use of these antimicrobials in animal feeding for prophylaxis and growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…The tet(O) gene is widespread in Campylobacter and has since been found in different Grampositive bacterial species including enterococci and streptococci [3,48,59,80], suggesting the Gram-positive origin of this gene. A high frequency of resistance to tetracycline (72%) has recently been reported among C. jejuni in Spain [43].…”
Section: Tetracycline Resistancementioning
confidence: 99%